2017
DOI: 10.1021/acsnano.7b03239
|View full text |Cite
|
Sign up to set email alerts
|

Bioengineering Bacterially Derived Immunomodulants: A Therapeutic Approach to Inflammatory Bowel Disease

Abstract: Bacterial enteric pathogens have evolved efficient mechanisms to suppress mammalian inflammatory and immunoregulatory pathways. By exploiting the evolutionary relationship between the gut and pathogenic bacteria, we have developed a potential mucosal therapeutic. Our findings suggest that engineered preparations of the Salmonella acetyltransferase, AvrA, suppress acute inflammatory responses such as those observed in inflammatory bowel disease (IBD). We created 125 nm diameter cross-linked protein nanoparticle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 62 publications
0
18
0
Order By: Relevance
“…Rather, invasion likely occurs only in a small number of cells, making such an analysis challenging and invasion difficult to detect in a mammalian in vivo infection model. Finally, the information generated in this study may be valuable, in light of the recent report of a study in which investigators exploited the inhibitory activity of AvrA on innate immunity in nanoparticles to treat inflammatory bowel disease (23). The nanoparticle study performed using AvrA revealed that expression of this class of protein at steady state in cells can by sufficient to dampen gut inflammation.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Rather, invasion likely occurs only in a small number of cells, making such an analysis challenging and invasion difficult to detect in a mammalian in vivo infection model. Finally, the information generated in this study may be valuable, in light of the recent report of a study in which investigators exploited the inhibitory activity of AvrA on innate immunity in nanoparticles to treat inflammatory bowel disease (23). The nanoparticle study performed using AvrA revealed that expression of this class of protein at steady state in cells can by sufficient to dampen gut inflammation.…”
Section: Discussionmentioning
confidence: 87%
“…AopP is proapoptotic due to it being a potent inhibitor of NF-B signaling (5), whereas AvrA is antiapoptotic due to its inhibitory activity against the JNK pathway (2,6). This property of AvrA has recently been exploited in the generation of nanoparticles harboring AvrA for the treatment of inflammatory bowel disease (23).…”
mentioning
confidence: 99%
“…Previous findings documented that overexpression of AvrA in transfected cells block activation of JNK (c-Jun N-terminal kinase), MAPK, NF-κB, and a range of inflammatory effector genes at the transcriptional level. Estrada et al used engineered AvrA to suppress inflammatory response similar to those observed in IBD [99]. Further, cross linking of AvrA to nanoparticles (AvrA-NPs) makes their internalization possible into epithelial and lamina porpria monocytic cells in both in vitro and in vivo models.…”
Section: Bacterially Derived Immunomodulantsmentioning
confidence: 99%
“…Further, cross linking of AvrA to nanoparticles (AvrA-NPs) makes their internalization possible into epithelial and lamina porpria monocytic cells in both in vitro and in vivo models. AvrA-NPs inhibit inflammatory pathways and reduce inflammation of tissues in murine models of colitis, thereby making bacterial protein-NP platforms effective therapeutics to fight chronic IBD [99].…”
Section: Bacterially Derived Immunomodulantsmentioning
confidence: 99%
“…69 Additionally, nanoparticles comprising an anti-inflammatory Salmonella acetyltransferase enzyme (AvrA) and crosslinked green fluorescent protein effectively treated acute inflammation characteristic of inflammatory bowel disease using a murine colitis model. 70…”
Section: Enzymes As Immunotherapeuticsmentioning
confidence: 99%